Evaluating connectivity models for conservation: insights from African lion dispersal patterns - Finerty, GE; Cushman, SA; Bauer, DT; Elliot, NB; Kesch, MK; Macdonald, DW; Loveridge, AJ (Springer Nature, 2023)
Context Evaluating connectivity and identifying corridors for protection is a central challenge in applied ecology and conservation. Rigorous validation and comparison of how approaches perform in capturing biological processes is needed to guide research and conservation action. Objectives We aim to compare the ability of connectivity surfaces optimised using home range and dispersal data to accurately capture lion movement during dispersal, using cost-distance and circuit theory approaches. Methods We delineate periods of dispersal in African lions (Panthera leo) to obtain movement trajectories of dispersing individuals across the Kavango Zambezi Transfrontier Conservation Area, southern Africa. We use these trajectories to assess comparative measures of connectivity values at dispersal points across surfaces and the ability of models to discriminate between observed and randomised paths. Results Encouragingly, results show that on average, all connectivity approaches and resistance surfaces used perform well in predicting movements of an independent set of dispersing lions. Cost-distance approaches were generally more sensitive to resistance input than circuit theory, but differences in performance measures between resistance inputs were small across both approaches. Conclusions Findings suggest that home range data can be used to generate resistance surfaces for connectivity maps in this system, with independent dispersal data providing a promising approach to thresholding what is considered as “connected” when delineating corridors. Most dispersers traversed through landscapes that had minimal human settlement and are likely highly connected by dispersal. Research into limiting factors and dispersal abilities will be critical to understanding how populations will respond to increasing habitat fragmentation and human expansion.